2020
DOI: 10.5539/ibr.v13n10p130
|View full text |Cite
|
Sign up to set email alerts
|

Financial and Non-Financial Measures in Evaluating Performance: The Role of Strategic Intelligence in the Context of Commercial Banks in Kenya

Abstract: This study provides comprehensive discussion on role of strategic intelligence in commercial banks, in Kenyan context. The primary focus was to evaluate the performance of commercial banks using both financial and non-financial performance measurers. The financial measurers comprised return on equity (ROE), while non-financial measures were customer satisfaction, learning and growth, and internal processes. The study was anchored on resource-based view and balanced scorecard model. The target population compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The research concluded that successful strategic planning helps a company's performance. Kori et al (2020) [22] tried to determine if strategic planning affects financial and nonfinancial performance in a business. Many empirical studies on the relationship between strategic planning and financial performance (Nambirajan & Prabhu, 2010 [23], Wolf & Floyd, 2017[24], George et al, 2019 [25]) suggest that the strategic planning construct can be measured as a single dimension, like a formal process.…”
Section: Strategic Planningmentioning
confidence: 99%
“…The research concluded that successful strategic planning helps a company's performance. Kori et al (2020) [22] tried to determine if strategic planning affects financial and nonfinancial performance in a business. Many empirical studies on the relationship between strategic planning and financial performance (Nambirajan & Prabhu, 2010 [23], Wolf & Floyd, 2017[24], George et al, 2019 [25]) suggest that the strategic planning construct can be measured as a single dimension, like a formal process.…”
Section: Strategic Planningmentioning
confidence: 99%
“…Homestay Performance: Kori, Muathe and Maina (2020), claimed that performance includes both financial and non-financial measurements, and is an indication of the capacity to meet the firm objectives. In addition, financial performance includes economic factors while non-financial performance includes success indicators like the market, quality of life, and customer satisfaction (Al-Mamary et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They increase customer base, in turn, catalyzes the efforts of any bank for achieving sustainability and increasing profitability (Badunenko, Kumbhakar, & Lozano-Vivas, 2021). Kori et al, (2020) also suggest that strategic internal factors enhances competitive advantage which is of utmost importance to enable a company to meet customer wants and needs effectively. Strategic internal factors in an organization is continuing to be an area that is receiving increased awareness, both in theory and practice especially in the banking industry (Abazeed, 2020) as the only option available for the industry to succeed in today's competitive business environment.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Strategic internal factors have an important role in every organizational setting (Kori, Muathe & Maina, 2020). Organizations have developed networked cooperation to develop their activities.…”
Section: Introductionmentioning
confidence: 99%